Conflict and Health - Roberts, Bayard; Polonsky, Jonathan; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Conflict and Health is a highly-accessed, open access journal documenting the public health impacts and responses related to armed conflict, humanitarian crises and forced migration. The journal provides a global platform to disseminate insightful and impactful studies. These span a broad range of public health topics including infectious disease prevention and control, nutrition, reproductive and maternal health, sexual and gender-based violence, mental health, non-communicable diseases, health systems, and ethics in conflicts and humanitarian crises. Supported by a global editorial board, Conflict and Health welcomes quantitative and qualitative studies and perspectives.
Keywords: Peace; Emergency medicine; Public health; Health promotion; Epidemiology; Public Health; Emergency Medicine; Health Promotion and Disease Prevention; Health Services Research; Epidemiology; Conflict Studies